On the use of research results contrary to their intended purpose (Diametros, 2009)
Double-application research is research whose results can become a source of knowledge, products, or technologies that are potentially useful to persons who intend to create threats to public health, agriculture, plants, animals, the environment, or inanimate matter. The great majority of double-application research has to do with genetic materials and the most commonly used classification includes six types of experiments. The harm that can result from the use of the results of such research in terrorist attacks is estimated to be greater than that of classical terrorist attacks. It is therefore necessary to propose measures that will limit or eliminate the risk that accompanies such experiments. Basic measures ought to include the inculcation of a proper attitude among researchers and auxiliary personnel, the preparation of ethical codes and legal regulations, the supervision of certain types of research, and care in the publication of research results that potentially have a double application. The method of limiting threats connected with these kinds of research should be adapted to the concrete situation of each country and the attainment of biological security must be based on the prompt, certain, and full identification of the threats. The basic responsibility in identifying double-character research should rest upon the researchers themselves (physicians, microbiologists, pharmacologists, and geneticists). It is necessary to prepare a unified, specialist code of ethics. In Poland activity aimed at securing biological security has consisted of drafting and ratifying the Act on genetically modified organisms (GMO) and the creation of a GMO Commission. Taking into consideration the experiences of other countries, these activities should be considered as fragmentary and inadequate.